To solve for x, we need to isolate x on one side of the equation.
First, let's add 7 to both sides of the equation to get rid of the -7 on the right side:
5 - 6x + 7 = -7 + 7
5 - 6x + 7 = 0
Combine like terms:
12 - 6x = 0
Now, let's subtract 12 from both sides of the equation to get rid of the 12 on the left side:
12 - 6x - 12 = 0 - 12
-6x = -12
Finally, divide both sides of the equation by -6 to solve for x:
-6x/-6 = -12/-6
x = 2
Solve 5−6x=−7
.(1 point)
3 answers
The equation 53x+113=−43
is solved as follows. Fill in the correct numbers to complete the solution.(1 point)
53x+113=−43
53x=
Subtract 113
from both sides.
x=
Multiply both sides by 35
, the reciprocal of 53
.
is solved as follows. Fill in the correct numbers to complete the solution.(1 point)
53x+113=−43
53x=
Subtract 113
from both sides.
x=
Multiply both sides by 35
, the reciprocal of 53
.
53x + 113 = -43
To solve for x, we need to isolate x on one side of the equation.
First, let's subtract 113 from both sides of the equation to get rid of the 113 on the left side:
53x + 113 - 113 = -43 - 113
53x = -156
Now, let's divide both sides of the equation by 53 to solve for x:
53x/53 = -156/53
x = -156/53
To solve for x, we need to isolate x on one side of the equation.
First, let's subtract 113 from both sides of the equation to get rid of the 113 on the left side:
53x + 113 - 113 = -43 - 113
53x = -156
Now, let's divide both sides of the equation by 53 to solve for x:
53x/53 = -156/53
x = -156/53